A Study on Synthesis and Characterization of Bio-Plastic Obtained from Potato (American Journal of Chemistry and Pharmacy, 2024)
The synthesis of bioplastic is a growing interest among researchers in today’s world. Starch extracted from potatoes was utilized to synthesize bioplastic. From raw potatoes starch was extracted after it was peeled, diced, crushed, blended, slurred, sedimented, filtered and oven-dried. The starch was made soluble in water with the help of acetic acid and was gelatinized by glycerol. Constant heat was supplied with regular stirring until homogenous gelatinous mixture was ready. The mixture was molded and dried to obtain bioplastic film. Physical and chemical properties were characterized. The film had average thickness of 3.45 ± 0.26 mm. The average density was 1.20 ± 0.04 g/cm3. The bioplastic revealed a biodegradability weight loss of 69.28 ± 1.52 % in 14 days. The water absorption of bioplastic was 81.08 ± 1.28 % in 2 hours. The opacity was measured 0.42 AUmm-1. Furthermore, Phenol, concentrated sulphuric acid, and concentrated hydrochloric acid made the bioplastic soluble whereas insoluble in water and wide range of organic solvents. The film had smooth and slightly sticky surface◦ with slight vinegar smell. The study has shown that starch from potatoes can be utilized to create bioplastic film as replacement for petroleum-based bioplastic.